The Bucket List Eco Experiences : traveling the world, sustaining the earth - Kinsman, Juliet, ....- (New York : Universe Publishing, 2022)
A bucket list focused on sustainable travel featuring 1,000 vacation ideas that are eco-friendly, respectful of local cultures, and highlight opportunities to give back A new era of sustainable travel is dawning - more than ever, vacationers are seeking experiences that are sustainable for the environment, sensitive of other cultures, make a positive impact, and above all, do no harm.Organized geographically, entries fall into broad types--accommodation, culture, food, nature, volunteering, and wildlife--so readers pinpoint what suits them best, whether "voluntourism" while studying endangered silverback gorillas in Uganda, rehabilitating orphaned penguins outside Cape Town, or visiting an eco-coffee plantation in Puerto Rico.
Keywords: Duurzaam Reizen; Duurzaam toerisme; Reizen; Toerisme